On Equilibrium When Contingent Capital Has a Market Trigger: A Correction to Sundaresan and Wang Journal of Finance (2015) - PENNACCHI, GEORGE; TCHISTYI, ALEXEI (Journal of Finance, 2019)
ABSTRACT This paper identifies an error in Sundaresan and Wang (2015, hereafter SW) that invalidates its Theorem 1. The paper develops a model of contingent capital (CC) with a stock price trigger that is consistent with SW's framework and yields closed‐form solutions for stock and CC prices. Yet, the model shows that unique stock price equilibria exist for a broader range of CC contractual terms than those required by SW. Specifically, when conversion terms benefit CC investors and penalize shareholders, a unique equilibrium can exist rather than the multiple equilibria stated in SW.